PENGEMBANGAN KOMODITAS UNGGULAN DI WILAYAH PENGEMBANGAN TUMPANG, KABUPATEN MALANG - Shinta Widyaning Cipta; Santun R.P. Sitorus; Djuara P. Lubis (Jurnal Kawistara, 2017)
Malang Regency is the one of regencies in East Java province which has the potential for the development of the agricultural sector. The role of the agricultural sector in GDP contribution toward Malang reached 35,04% in 2013. This becomes the input for the government to move the rural agricultural sector in order to increase the regional economy. This research aims to identify leading commodities, to analyze region hierarchy,  and to analyze development direction of the leading commodities. Data in this study were obtained from relevant agencies as well as through direct observation and interviews of stakeholders. They were chosen with purposive sampling method. Methods of data analysis using the LQ and SSA, schallogram, GIS, AHP–TOPSIS, and A’WOT. The results showed that superior priority commodities that will be developed in four sub-district is rice, mustard greens, cabbage, corns, and apples. The criteria of the region which became the leading commodities development priorities are areas of the base, the region at the hierarchy III, and land area that has suitable and available. Development direction was divided into four priorities, namely: priority 1 is Poncokusumo area of 4.221 ha, priority 2 is Wajak area of 1.270 ha, priority 3 is Tumpang area of 1.526 ha, and priority 4 is Jabung area of 1.315 ha. There are eight priority strategies that can be applied to develop leading commodites in Tumpang development area.